An unusual complication of nasolabial flap reconstruction - Mann, R (Ann R Coll Surg Engl, 2017)
Squamous cell carcinoma is the most common carcinoma in the oral cavity. Resection of these cancers often requires reconstruction. Nasolabial flaps are a robust and reliable local flap that provide a satisfactory outcome. We report two cases where an epidermoid cyst developed within the scar of the nasolabial flap and review the literature.